Unsur-unsur Budaya Jawa dalam Kitab Tafsir al-Ibriz Karya KH. Bisri Mustofa (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
A mufassir interprets and tries to express the meaning of the Qur'an. He is influenced by the culture that surrounds it. This can be seen from Tafsir al-Ibrīz  by KH. Bisri Mustofa. It contains many interesting Javanese cultural elements. He interprets the Qur'an without breaking away from the habits of the Javanese people, so that in explaining a verse it has various forms that can be accepted by the community. This paper argues that first, the interpreter's social space influenced in various forms of his interpretation of the Qur'an. Second, the vernacularization process contributes  the forms of interpretation of the Qur'an because it involves various elements of locality within it. Third, many elements of local culture appear, al-Ibrīz  as a reference for interpretation in Javanese pegon also talks about religious issues and conversations base on Javanese society. By using Koentjaraningrat theory, this study analyzes verses that contain elements of Javanese culture, including the religious system and religious ceremonies. This paper shows that Tafsir al-Ibrīz  contains these Javanese elements, including studies on beliefs in supernatural spirits, supernatural powers and religious ceremonies in the form of tahlil, as well as things that make KH. Bisri Mustofa interpreted the Qur'an by bringing up Javanese culture.